2012
DOI: 10.1007/s00436-012-2987-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical tools for the removal of Ixodes ricinus female ticks—differences of instruments and pulling or twisting?

Abstract: The fast and safe removal of ticks is of medical and veterinary importance since many tick-borne pathogens require time to be transmitted. In the past, many tools and applications were used to remove ticks from the skin of humans and pets. Choking the ticks by blocking their respiratory system with chemicals cannot be recommended due to the low respiratory rate of ticks. Mechanical devices to remove ticks are usually recommended; however, they vary with regard to their mechanism of seizing and holding the tick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 14 publications
0
21
0
1
Order By: Relevance
“…50 Usually, a tick check would be done after leaving a risk area, although it also is prudent to check for ticks that might be moving over clothing or skin while in tick habitats, although this would seem to be rarely done by exposed persons. 51 Removal of attached ticks is ideally done with fine-tipped, stiff, and angled forceps (tweezers) placed around the head of the tick as near as is possible to the skin, followed by a steady, upward pulling movement [52][53][54][55] (Fig. 1).…”
Section: Tick Checksmentioning
confidence: 99%
“…50 Usually, a tick check would be done after leaving a risk area, although it also is prudent to check for ticks that might be moving over clothing or skin while in tick habitats, although this would seem to be rarely done by exposed persons. 51 Removal of attached ticks is ideally done with fine-tipped, stiff, and angled forceps (tweezers) placed around the head of the tick as near as is possible to the skin, followed by a steady, upward pulling movement [52][53][54][55] (Fig. 1).…”
Section: Tick Checksmentioning
confidence: 99%
“…If this happens, the mouth-part should be removed with tweezers. Ducher et al [24] observed that rotation seems to require less force and though breaking of the hypostome was more frequent in this technique, the part left in the wound was shorter than after removal by pulling. They also remarked that less time is needed to extract female tick when rotation is used [24].…”
Section: Tick Removalmentioning
confidence: 90%
“…The experimental evidences to support the most suggested strategies of tick removal are still lacking [1]. For tick removal, a wide range of tools can be applied, including chemicals and mechanical treatment [24]. There are commercially available devices like tick tool, tick twister, tick nipper, tick key, pro ticked off [1].…”
Section: Tick Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…Pour retirer une tique il est préférable d'utiliser des pinces à épiler avec des extrémités rigides et en angle placées près de la tête de la tique et aussi près de la peau que possible, et de tirer en effectuant un mouvement vers le haut (34,37,38,39)…”
Section: Prévention De La Maladie De Lyme Par Des Vêtements Appropriéunclassified